The Impact of Targeted Soccer Training Interventions on YO–YO Intermittent Recovery Test Performance in University-Level Soccer Players - Saha, Gopal Chandra; Shaw, Chandan; Orhan, Bekir Erhan; Karak, Prem Kumar; Mondal, Smriti; Halder, Shantanu; Biswas, Subhashis; Roy, Bidya (Physical Education Theory and Methodology, 2025)
Background. Soccer demands high endurance, speed, and aerobic capacity, making fitness a key performance factor. The Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) is a valid field test to assess these attributes in soccer players. Objectives. This study aimed to evaluate the effect of a 12-week targeted soccer training program on aerobic endurance in university-level male soccer players. Materials and methods. A quasi-experimental pretest-posttest design was used, involving 40 university-level male soccer players (aged 17–25) from Visva-Bharati University. Participants underwent a 12-week targeted soccer training program. Aerobic endurance performance was assessed using the YYIR1 test, evaluating accumulated distance, cumulative time, and VO₂ max before and after the intervention. Data were analyzed using paired-sample t-tests, with asignificance level set at p < 0.05. Results. Among 32 university-level male soccer players, significant improvements were observed in the post-interventionperiod: accumulated distance (mean increase = 312.5 meters, d = 1.70), cumulative time (mean increase = 2.54 minutes, d = 1.80), and VO₂ max (mean increase = 2.62 ml/kg/min, d = 1.72), all with p < 0.001. Conclusions. According to the study, it was found that the 12-week targeted soccer training intervention led to statistically significant enhancements in aerobic endurance capacities among university-level soccer players, as demonstrated by improvements in YYIR1 test outcomes.